(untitled) (The Planet, 2024)
Introduction: Congenital heart disease (CHD) represents a significant challenge for pregnant women due to the increased hemodynamic demands of pregnancy. Pregnancy in such cases poses an elevated risk of adverse events, including heart failure, arrhythmias, and thromboembolic events. Maternal complications can lead to increased maternal morbidity and mortality. Aim of the study: This study aimed to analyze the complications experienced by pregnant women with congenital heart disease with a specific focus on maternal and fetal outcomes. Methods and materials: This was an observational study that was conducted in the Combined Military Hospital (CMH) Dhaka, Bangladesh from January 2020 to December 2021. In total 30 pregnant women with congenital heart disease were enrolled in this study as the study subjects. A convenient purposive sampling technique was used in sample selection. All data were processed, analyzed, and disseminated by using MS Office tools. Results: In this study, obstetric complications included pre-eclampsia (10%), placenta previa (3%), placental abruption (3%), and hemorrhage (7%), while pre-term delivery affected 17% of pregnancies. Fetal complications comprised foetal distress (10%), foetal growth restriction (7%), foetal malformations (20%), neonatal death (7%) and foetal stillbirth in 2 cases (7%). Conclusion: Pregnant women with congenital heart disease often face common obstetric complications like pre-eclampsia, placenta issues, and bleeding. Premature births and prolonged pregnancies add to the challenges. Fetal complications include distress, growth issues, and malformations, reflecting the complexity of these pregnancies; some cases result in fetal stillbirth and neonatal death.